AN ANALYSIS OF CATEGORY SHIFT IN SUBTITLE ALICE IN WONDERLAND MOVIE BY TIM BURTON - Asyita Anisni; Evert H. Hilman (IKIP Siliwangi, 2023)
The purpose of this research was conducted to prove whether â€œtranslation shiftâ€Â is still relevant to convey messages in translation with this strategy to procedure relatively accurate translation, and what types and shift categories can help researchers convey messages from the source language to the target language. This research uses descriptive qualitative research by collecting and analyzing Indonesian and English subtitles from Alice in Wonderland movie by Tim Burton using J.C Catford's theory of translation shift. This paper produced 462 data. which were analyzed qualitatively to determine the types of translation shifts employed. There are 48% structure shifts, 5% class shifts, 35% unit shifts, and 12% intra-system. Based on the data analyzed, the most dominant shift that occurs is the structure shift.Â Keywords:Â Movie; Translation Shift; Translation Quality Assessment; Subtitle